Multi-scale cost-benefit analysis of the Los Angeles Soft-Story Ordinance. (1st July 2020) - Yi, Zhengxiang; Burton, Henry V.; Shokrabadi, Mehrdad; Issa, Omar
Highlights: Multiscale cost-benefit analysis performed for Los Angeles Soft-Story Ordinance. Implemented intensity- and time-based assessment for individual buildings. Portfolio-scale cost-benefit evaluation conducted for hypothetical M 7.1 Puente Hills event. Stochastic-event-set-based assessment performed at the portfolio scale. Abstract: A multi-scale (building-specific and portfolio) cost-benefit analysis of the Los Angeles soft-story Ordinance for woodframe residential buildings is presented. Building-specific loss functions (shaking intensity versus loss ratio) are computed by implementing the FEMA P-58 seismic loss assessment methodology on a set of archetype buildings that reflect the variations in key structural characteristics (e.g. 1st story wall layout, number of stories) of the approximately 12, 000 buildings affected by the Ordinance. The cost-benefit ratio is assessed as the retrofit cost divided by the reduction in earthquake-induced losses that result from the retrofit. At the individual building level, both intensity and time-based cost-benefit assessments are performed. The latter uses the expected annual losses to determine the break-even time, which is the duration needed to recoup the upfront cost of the retrofit. The average break-even time when considering all archetypes is four to five years. At the portfolio-scale, an average cost-benefit ratio of 0.32 is obtained for a hypothetical Mw 7.1 Puente Hills scenario earthquake. A first-of-its kind stochastic event-set cost-benefit assessment is also performed, where all events (approximately 8000) that are significant to the region are considered. From this assessment, it was determined that the probability of achieving a desirable cost-benefit ratio (value between 0.0 and 1.0) within a 50-year period is approximately 0.9.